Development of GoEliTool using Iterative Incremental Approach - Rosa Delima; Joko Purwadi (CCIT (Creative Communication and Innovative Technology) Journal, 2024)
GoEliTool is a tool for requirements elicitation during the requirements engineering process. Such a tool is specifically developed for elicitation through a goal-oriented requirements engineering (GORE) approach. GoEliTool was developed in the previous study. However, the first version of the tool still had many limitations to be corrected so that the process of data elicitation from stakeholders could be carried out more easily and effectively. In this study, the development of the tool was performed through an iterative, incremental approach based on the limitations found in the previous version. The development process consisted of three cycles, and there were three iterations in the second cycle. The tool test was conducted using a black box approach, and the user satisfaction test was conducted using two test questionnaires, namely the User Experience Questionnaire (UEQ) and the System Usability Scale (SUS) questionnaire. The results of the black box test showed that the tool was able to work according to the test scenario. Furthermore, user satisfaction using the UEQ questionnaire showed that the tool was in the above-average category. Regarding the SUS questionnaire, it obtained a grade C result, which indicated the marginal acceptance category.